Additive for lithium ion secondary battery positive electrode using electrolytic solution, lithium ion secondary battery positive electrode material, and lithium ion secondary battery

CN122996519APending Publication Date: 2026-10-27UNIV OKAYAMA +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023954.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2025-03-25
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0035]根据本发明,能够提供一种可以改善使用电解液的锂离子二次电池的输入输出特性的锂离子二次电池正极的添加材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

Provided is an electrode-electrolyte interface resistance R2-reducing additive material for a lithium ion secondary battery electrode other than a ferroelectric, which can improve input / output characteristics, and a lithium ion secondary battery positive electrode material and a lithium ion secondary battery including the same. An additive material for a lithium ion secondary battery positive electrode, characterized by: a composite oxide coexisting with a lithium ion secondary battery positive electrode material including cations of one or more elements selected from among Mn, Fe, Ni, and Co, the composite oxide not including alkali metal ions and alkaline earth metal ions, having both acid sites and base sites, and having a relative dielectric constant of 20 or more; and a lithium ion secondary battery positive electrode material and a lithium ion secondary battery including the additive material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to additives for the positive electrode of a lithium-ion secondary battery using an electrolyte, positive electrode materials for lithium-ion secondary batteries, and lithium-ion secondary batteries. Background Technology

[0002] Lithium-ion secondary batteries are widely used in electronic and communication devices, and in applications such as automotive and energy storage devices. One technique to improve the characteristics of lithium-ion secondary batteries is the use of additive materials (composite oxides).

[0003] Patent Document 1 discloses a positive electrode material for lithium-ion secondary batteries comprising positive electrode active material particles and a ferroelectric material, wherein the ferroelectric material is disposed on at least a portion of the surface of the positive electrode active material particles. This results in excellent output characteristics in low-temperature environments.

[0004] Patent document 2 discloses a non-aqueous electrolyte secondary battery that uses a ferroelectric material with a relative permittivity of 500 or higher sintered on the surface of the positive electrode active material. Therefore, it is generally believed that sufficient output characteristics can be obtained even in low-temperature regions.

[0005] Patent document 3 discloses a positive electrode material for lithium-ion secondary batteries, which contains cation A with an ionic radius smaller than lithium ions and a valence of 2 or higher, and cation B with an ionic radius larger than lithium ions and a valence of 2 or higher, in the interlayer spaces of the layered crystalline structure. Furthermore, typical elements of cation A and cation B are disclosed for manufacturing the positive electrode material for lithium-ion secondary batteries. Therefore, it is generally considered that this material can be used as a positive electrode for lithium-ion secondary batteries with high output characteristics.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-181614

[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-210694

[0010] Patent Document 3: Japanese Publication No. 2023-52895 Summary of the Invention

[0011] The technical problem that the invention aims to solve

[0012] To improve the input-output characteristics (rate characteristics) of lithium-ion secondary batteries, reducing the internal resistance is important. The internal resistance R... tIt can be roughly divided into the internal resistance of the electrode material (active substance) R1, the interfacial resistance between the electrode and the electrolyte R2, and the electrolyte (diffusion) resistance R3.

[0013] R t =R1 + R2 + R3

[0014] Patent document 3 improves input-output characteristics by reducing the internal resistance R1 of the cathode material particles. While reducing the internal resistance R1 of the cathode material particles to improve input-output characteristics is important, the largest of the internal resistances is the electrode-electrolyte interface resistance R2. Reducing this resistance can effectively improve the input-output characteristics of the lithium-ion secondary battery.

[0015] Patent documents 1 and 2 improve low-temperature output characteristics by reducing the electrode-electrolyte interfacial resistance R2, but these are also solutions that allow ferroelectric materials to coexist in order to reduce the interfacial resistance R2. The inventors of this invention discovered that because the ferroelectric material contains alkaline earth metal ions, there is a problem that these components react with the alkaline earth metal ions when combined with cathode materials containing Mn, Ni, Fe, Co, etc. Similarly, it was also discovered that alkali metal ions react with these components.

[0016] Therefore, in order to improve the input and output characteristics of lithium-ion secondary batteries, reducing the electrode-electrolyte interface resistance R2 is effective, and new materials other than ferroelectrics are expected to reduce the electrode-electrolyte interface resistance R2.

[0017] The present invention was made in view of the above-mentioned problems. The objective is to provide an effective lithium-ion secondary battery electrode, in particular a positive electrode additive material, that can reduce the interfacial resistance R2 of the electrode-electrolyte in a lithium-ion secondary battery positive electrode material containing one or more cations of Mn, Fe, Ni, and Co, and improve the input-output characteristics of the electrode material.

[0018] Methods for solving technical problems

[0019] The inventors of this invention conducted in-depth research to solve the aforementioned technical problems. As a result, they discovered that by coexisting a composite oxide containing both acid and base sites and having a relative permittivity of 20 or higher with a lithium-ion secondary battery cathode material, the input-output characteristics can be improved. This invention is derived from further research based on the above insights, and its main contents are as follows.

[0020] [1] An additive material is an additive material for the positive electrode of a lithium-ion secondary battery using an electrolyte, characterized in that,

[0021] The additive material comprises a composite oxide that coexists with a lithium-ion secondary battery cathode material containing cations of one or more elements selected from Mn, Fe, Ni, and Co. The composite oxide does not contain alkali metal ions or alkaline earth metal ions, has both acid sites and alkaline sites, and has a relative permittivity of 20 or higher.

[0022] [2] The additive material as described in [1] is characterized in that,

[0023] The composite oxide has the following composition formula: M x Zr 1-x O 2-y Element M contains trivalent metal ions, and the molar ratios x and y satisfy 0 < x < 1 and 0 < y < 0.5, respectively.

[0024] [3] The additive material as described in [2] is characterized in that,

[0025] The M comprises one or more trivalent metal ions selected from La, Pr, Sm, Nd, Gd, Yb, Ho, and Y.

[0026] [4] The additive material as described in [2] or [3] is characterized in that,

[0027] The M contains a Ce metal ion.

[0028] [5] The additive material as described in any one of [1] to [4], characterized in that,

[0029] The specific surface area of ​​the composite oxide is 35 m². 2 / g or more.

[0030] [6] A positive electrode material for a lithium-ion secondary battery, characterized in that,

[0031] It includes any of the additives described in [1] to [5].

[0032] [7] A lithium-ion secondary battery, characterized in that,

[0033] It includes the lithium-ion secondary battery cathode material as described in [6].

[0034] Invention Effects

[0035] According to the present invention, an additive material for the positive electrode of a lithium-ion secondary battery that can improve the input-output characteristics of a lithium-ion secondary battery using an electrolyte can be provided. Attached Figure Description

[0036] Figure 1 This is an equivalent circuit diagram used to determine the resistance of interfacial charge movement (LiCoO2 = LCO reference).

[0037] Figure 2 It is used to determine the interfacial charge transfer resistance (LiNi). 0.5 Co 0.2 Mn 0.3 Equivalent circuit diagram of O2 (NCM reference). Detailed Implementation

[0038] Additives for the cathode of lithium-ion secondary batteries

[0039] The following describes the additives for the positive electrode of a lithium-ion secondary battery using the electrolyte of the present invention.

[0040] The additive material for the positive electrode of the lithium-ion secondary battery of the present invention (hereinafter referred to as "additive material") is used in the assembly of lithium-ion secondary batteries, the fabrication of lithium-ion secondary battery positive electrode sheets, and the manufacturing of lithium-ion secondary battery positive electrode materials.

[0041] The additive material of the present invention is a composite oxide that coexists with a lithium-ion secondary battery cathode material containing one or more cations of elements including Mn, Fe, Ni, and Co. The composite oxide does not contain alkali metal ions or alkaline earth metal ions, has both acid sites and alkaline sites, and has a relative permittivity of 20 or higher.

[0042] The cathode material of a lithium-ion secondary battery is a lithium-containing transition metal composite oxide containing one or more cations from elements such as Mn, Fe, Ni, and Co, for example, LiMn2O4 or LiNi. x Co y Mn z O2(x+y+z=1), LiNi x Co y Al x O2(x+y+z=1), LiNi x Mn y O4 (x+y=1), LiCoO2, LiFePO4, Li (Fe x Mn y )PO4 (x+y=1), xLi2MnO3-(1-x)LiMeO2 (Me=Ni, Co, Mn), Li2MnO x F y Li-containing compounds such as (x + y = 3). The additive material of the present invention is not only effective in LiCoO2, but also in other cathode materials, and can be widely used in various cathode materials.

[0043] The additive material of this invention comprises a composite oxide that does not contain alkali metal ions or alkaline earth metal ions. In the case of a composite oxide containing alkali metal ions or alkaline earth metal ions, since it reacts when coexisting with a cathode material containing a lithium transition metal composite oxide containing one or more cations of Mn, Fe, Ni, or Co, the additive material of this invention is designed to be a composite oxide that does not contain alkali metal ions or alkaline earth metal ions. The cations Mn, Fe, Ni, and Co contained in the cathode material are acidic oxide components; therefore, in a composite oxide containing alkali metal ions or alkaline earth metal ions as basic oxide components, the acidic oxide component and the basic oxide component will undergo an acid-base reaction.

[0044] The composite oxide further comprises both acid sites and basic sites. It is believed that the acid sites and basic sites exert the effects of the invention through the following mechanism.

[0045] In the electrolyte of lithium-ion secondary batteries, it is known that organic solvent molecules in lithium ions undergo solvation. Specifically, during the movement of charge at the interface between the positive electrode material and the electrolyte in a lithium-ion secondary battery, lithium ions moving towards the positive electrode in the electrolyte cause desolvation of the solvated lithium ions, or lithium ions entering the electrolyte from the positive electrode cause solvation. This desolvation or solvation of lithium ions constitutes the charge movement resistance at the interface between the positive electrode material and the electrolyte, increasing the proportion of internal resistance in the lithium-ion secondary battery. That is, this resistance hinders the high output characteristics (rate characteristics) of the lithium-ion secondary battery. In this invention, by coexisting the additive material of this invention with the positive electrode material, the charge movement resistance at the interface between the positive electrode material and the electrolyte can be reduced, improving the high output characteristics of the lithium-ion secondary battery. That is, the additive material of this invention is a composite oxide having both acid sites and alkaline sites. Therefore, the positively charged lithium ions with solvation readily adsorb onto alkaline sites (negative fraction), and the negative fraction of the solvated solvent molecules readily adsorbs onto acid sites (positive fraction). In other words, when both adsorb onto the additive material, the charge-depleted portion of the solvated lithium ions tends to neutralize within the additive material (the positive charge of the lithium ions accepts electrons from the additive material, while the negative charge-depleted portion of the solvated molecules accepts electrons from the additive material). As a result, the electrostatic attraction between the solvation and lithium ions weakens, making desolvation easier.

[0046] On the other hand, when the positive electrode material receives lithium ions (during discharge), electrons are injected into the positive electrode material via the current collector, making it prone to becoming negatively charged. While this is beneficial for attracting lithium ions, it makes it difficult to desolvate the solvated molecules of lithium ions. When the additive material of the present invention, which is an electronic insulator, coexists, the injected electrons cannot reach the additive material, and therefore will not become negatively charged like the positive electrode material.

[0047] During charging (when lithium ions are released from the positive electrode material into the electrolyte), the effect of the additive material of the present invention can be explained in contrast to the above description.

[0048] The composite oxide included in the additive material of this invention has a relative permittivity of 20 or higher. It is believed that during the charging and discharging of a lithium-ion secondary battery, the surface of the composite oxide of the additive material becomes polarized due to the electric field, causing solvated lithium adsorption and promoting desolvation or solvation. That is, when the composite oxide is an insulator with a large relative permittivity, a large polarization is caused by the electric field gradient within the lithium-ion secondary battery. This effect, combined with the aforementioned acid and base sites, facilitates the desolvation or solvation of lithium ions, achieving the desired effect of this invention. When the relative permittivity of the composite oxide is less than 20, the electric field gradient within the lithium-ion secondary battery cannot cause sufficient polarization, and the synergistic effect of the aforementioned acid and base sites is not obtained. As a result, the input-output characteristics of the lithium-ion secondary battery are not sufficiently improved. Therefore, a relatively large relative permittivity of the composite oxide is preferred, with no upper limit, but currently, there are no paraelectric oxides with a relative permittivity of 500 or higher.

[0049] The relative permittivity referred to in this invention is the ratio of the permittivity of each composite oxide to the permittivity of vacuum. Permittivity is an indicator of ease of polarization; the higher the permittivity, the higher the relative permittivity. That is, the higher the relative permittivity, the easier it is for the additive material (containing the composite oxide) to polarize. Based on the above, a relative permittivity of 30 or higher is preferred, and more preferably 40 or higher.

[0050] In this invention, the acid sites and base sites refer to the values ​​measured by temperature-programmed desorption (TPD) during the adsorption and desorption of ammonia (NH3) as acid sites, and the values ​​measured by the adsorption and desorption of carbon dioxide (CO2) as base sites. The test sample is pre-treated to adsorb the ammonia or carbon dioxide standard substance, and then the sample is heated while the amount of the standard substance being desorbed is measured to determine the acid sites or base sites and their amounts. Specifically, as a pretreatment, the test sample is heat-treated at 370°C for 30 minutes in a 20% O2 / He environment, and then the sample is exposed to the ammonia or carbon dioxide standard substance at 50°C for 30 minutes to allow it to adsorb the standard substance. Subsequently, the temperature is increased from 50°C to 500°C at a rate of 20°C / min, and the amount of standard substance desorbed during this process is measured.

[0051] In this invention, having acid sites and basic sites means that the amount of acid sites measured at 50°C to 500°C is 0.25 mmol / g or more, and the amount of basic sites measured at 50°C to 500°C is 0.18 mmol / g or more. The amount of acid sites measured at 50°C to 500°C is preferably 0.30 mmol / g or more, and more preferably 0.40 mmol / g or more. The amount of basic sites measured at 50°C to 500°C is preferably 0.25 mmol / g or more, and more preferably 0.35 mmol / g or more.

[0052] Furthermore, the preferred maximum value (peak value) of the NH4-TPD curve is 3.0 × 10⁻⁶. -4 mmol / g·sec or higher. The preferred maximum value (peak value) of the CO2-TPD curve is 2.5 × 10⁻⁶. -4 mmol / g·sec or higher.

[0053] The measuring apparatus used was the BELCAT-A manufactured by BEL, Japan. NH3 was used for evaluating acidic sites, and CO2 was used for evaluating basic sites. A TCD (Thermal Conductivity Detector) was used as the detector.

[0054] As a pretreatment, the sample was treated at 370°C for 30 minutes in a 20% O2 / He environment, followed by exposure to a standard at 50°C for 30 minutes to allow the standard to adsorb. Subsequently, the temperature was increased from 50°C to 500°C at a rate of 20°C / min, and the amount or temperature of the standard that was removed was evaluated.

[0055] The composite oxide included in the additive material of this invention coexists with the positive electrode material of a lithium-ion secondary battery. This means, as described above, that it is added during the assembly of the lithium-ion secondary battery, the fabrication of the positive electrode sheet, and the manufacturing of the positive electrode material. Generally, the positive electrode material of a lithium-ion secondary battery can be dispersed on the surface or within the positive electrode layer formed on the current collector. Therefore, it is preferable that the composite oxide, as an additive material, coexists near the positive electrode material on the surface or within the positive electrode layer; more preferably, the composite oxide, as an additive material, is in contact with and coexists with the positive electrode material on the surface or within the positive electrode layer. Furthermore, it is ideal that all the added composite oxide is in the aforementioned state, but even a portion of it being in the aforementioned state is sufficient to fully exert the effects of this invention.

[0056] The term "near the positive electrode material of the lithium-ion secondary battery" refers to the distance at which lithium ions, desolvated on the surface of the added composite oxide, can reach the positive electrode material without being resolvated in the solvent. For example, this distance is 100 nm or less, more preferably 50 nm or less, and even more preferably 25 nm or less.

[0057] The composite oxide contained in the additive material of the present invention preferably comprises a substance with smaller particles than the cathode material of a lithium-ion secondary battery. For example, in an average particle size D 50 Among them, D is the preferred option. 50 (Composite oxide) <D 50 The relationship between (positive electrode material) and D. A more preferred D. 50 (Composite oxide) < [D] 50 The relationship between (positive electrode material) / 10]. Furthermore, D 50 It is the particle diameter with a cumulative frequency of 50% based on volume, also known as the median particle diameter.

[0058] The composite oxide contained in the additive material of the present invention preferably contains at least 35% by volume particles with a diameter of 1 μm or less, and more preferably at least 45%. Smaller particles of the composite oxide have a greater effect, therefore, the aforementioned particle content is preferred. That is, a larger number of particles, in a state of attachment to or close to the particles of the cathode material, is preferred. On the surface of the composite oxide, which is the additive material of the present invention, lithium ions are desolvated or solvated as described above, and this state is even more preferred for more efficient supply of lithium ions to the particles of the cathode material.

[0059] The composite oxide of the present invention is an oxide containing two or more positive ions (cations), or it can be (M 1 M 2 M 3 M 4 M n O x Such oxides. Among them, M, for the reasons mentioned above... 1 M 2 M 3 M 4 M n It does not contain alkali metal ions or alkaline earth metal ions. M x O y Simple oxides cannot satisfy the requirement of having both acid and basic sites, thus failing to achieve the desired effects of this invention. To achieve both acid and basic sites, this can be accomplished by appropriately combining multiple cations. This is because combining multiple cations with different valences or electronegativity creates a strongly polarized state on the surface of the composite oxide, thereby forming acid and basic sites. The polarization state varies depending on the coordination state of the cations or the crystal structure of the composite oxide, and their combination is not regular. To obtain the effects of this invention, it is necessary to determine the acid and basic sites as described above. Further preferably, oxygen vacancies are formed. Acid and basic sites based on the presence of oxygen vacancies are easily formed.

[0060] The composite oxide is

[0061] Composition M x Zr 1-x O 2-y ...Composition formula (1)

[0062] It is preferable that M contains trivalent metal ions. Zirconium (Zr) ions are preferred as a component of the additive material in the battery because they are stable for redox reactions and are difficult to dissolve as a single cation. Furthermore, by replacing part of the zirconium oxide (ZrO2) with trivalent cation M, oxygen vacancies are formed, thus acid sites and base sites can be formed more effectively as described above, which is even more preferable. 0 < x < 1 and 0 < y < 0.5 are acceptable, but from the viewpoint of the degree of association of the formed oxygen vacancies, 0 < x < 0.9 and 0 < y < 0.45 are more preferable, and 0.1 < x < 0.6 and 0.05 < y < 0.3 are even more preferable. In addition, the composite oxide of formula (1) is preferably cubic or pseudo-cubic.

[0063] The M is preferably a trivalent cation of rare earth elements, scandium, or yttrium. More preferably, the M is a composite oxide containing one or more trivalent metal ions selected from La, Pr, Sm, Nd, Gd, Yb, Ho, and Y. The oxygen vacancies formed by these cations can easily form acid sites and basic sites through effective configuration. Furthermore, sometimes the M is preferably a composite oxide containing multiple types of cations.

[0064] The M is preferably a metal ion containing Ce. The valence of the Ce metal ion (cation) is preferably tetravalent. Tetravalent M cannot form oxygen vacancies, but it has a higher electron density than Zr ions, thus increasing the relative permittivity of the composite oxide, making it more preferable. The Ce content in the composite oxide, in terms of the Ce / (Ce+Zr) molar ratio, is preferably 0.05 to 0.9, more preferably 0.1 to 0.8, and even more preferably 0.1 to 0.6.

[0065] The composite oxide contained in the additive material of the present invention preferably has a specific surface area of ​​35 m². 2 / g or more. Specific surface area is 35m². 2 With a concentration of 1 g or more, the number of solvation and desolvation sites for lithium ions increases, thus making the effects of the present invention more significant. Alternatively, sufficient effects can be obtained with a small amount of added material. Based on the foregoing reasons, the specific surface area can be larger, preferably 55 m² / g. 2 For g or above, 60m is preferred. 2 / g or more, 70m 2 / g or more, 80m 2 / g or more, 90m 2 / g or more, 100m2 / g or more, 150m 2 / g or more. While further increasing the specific surface area of ​​the composite oxide is achievable experimentally, from an industrial perspective, 200m² is less feasible. 2 / g is set to the maximum.

[0066] Specific surface area can be determined as follows: As a pretreatment, about 0.3 g of the sample is placed in a flask-type sample cell and degassed at 370°C for 40 minutes under nitrogen flow using a FloVac degassing device (manufactured by Anton-Paar Japan). Then, the surface area is measured by the BET method (1-point method) based on nitrogen adsorption using an Anton-Paar Japan NOVA touch NX-4LX-1 surface area measuring device (manufactured by Anton-Paar Japan).

[0067] Next, a method for manufacturing additives for the positive electrode of a lithium-ion secondary battery using the electrolyte of the present invention will be described.

[0068] The additive material for the positive electrode of a lithium-ion secondary battery using the electrolyte of the present invention can be any method that can produce a composite oxide that satisfies the elements of the present invention. Examples include solid-state reaction, chemical vapor deposition, hydrothermal synthesis, wet synthesis, sol-gel method, and spray pyrolysis.

[0069] Below, an example of synthesis via wet synthesis is shown.

[0070] First, the raw material containing the composite oxide of the additive is dissolved in water to prepare an aqueous solution. Examples of the raw material include water-soluble salts such as nitrates, chlorides, sulfates, and acetates. Specific examples of the raw material include zirconium oxychloride and cations other than zirconium such as La, Pr, Sm, Nd, Gd, Yb, Ho, Ce, and Y, using their chlorides. These raw materials are dissolved in water (preferably pure water or ion-exchanged water) at a specified molar ratio to obtain an aqueous solution containing all the raw materials. The method of dissolution and stirring is not particularly limited.

[0071] Next, a precipitant is added to the raw material aqueous solution to co-precipitate the composite oxide raw materials, obtaining a precipitate (slurry). The precipitant is, for example, a pH-controlled pH range that allows the metal ions to precipitate. Typically, precipitation can be achieved by adding alkaline compounds such as ammonia, hydroxides (NaOH, KOH, etc.) to raise the pH (making it alkaline). Preferably, the precipitated slurry is heated to 70–90°C. The heating method is not particularly limited. Heating the slurry means promoting aeration or oxygen bridging reactions in the precipitate. For example, the obtained slurry is heated to between 70 and 90°C and maintained for 4–10 hours (maturation). During this maturation, it is more preferable to perform industrially common stirring operations such as stirring with agitator blades or circulation via a pump.

[0072] Alternatively, the precipitant can be added while the raw material aqueous solution is heated. Heating the raw material aqueous solution alters the nucleation behavior, thereby changing the aggregation structure of the precipitate.

[0073] The matured slurry undergoes solid-liquid separation and washing. The method of solid-liquid separation is not limited; industrial equipment such as centrifuges and filters can be used. The washing operation aims to reduce chloride ions in the hydroxide slurry containing zirconium and other cations as raw materials for the complex oxide. This is achieved, for example, by dispersing the hydroxide in pure water and then using a centrifuge or filter. Preferably, this washing operation continues until the chloride ion content in the hydroxide is below 3% by mass.

[0074] The precipitate containing the cleaned zirconium and other cations is then dried. The drying process utilizes industrially available externally heated or internally combusted drying equipment, for example, at a temperature of approximately 100–200°C using hot air or a heater. Spray drying can also be employed.

[0075] After drying, firing continues. The temperature of the firing furnace is appropriately determined in a manner that satisfies the elements of the present invention, in conjunction with the precipitation and drying conditions, for example, set to 400–900°C. The firing time is typically between 30 minutes and 10 hours, and is appropriately determined, similarly, in a manner that satisfies the elements of the present invention, as with the firing temperature. Furthermore, the aforementioned drying and firing operations can be performed as separate operations or as a series of continuous operations. Alternatively, the precipitate can be fired directly without a drying process.

[0076] Composition M x Zr 1-x O 2-y In this case, the preferred firing conditions are those for pseudo-cubic crystals. For example, firing at a temperature of 900°C or below. More preferably, firing at 600°C or below.

[0077] Through a firing process, the hydroxides containing zirconium and other cations, which serve as raw materials for the composite oxide, are dehydrated to form their composite oxides. The composite oxides obtained in this way can also be pulverized as needed to adjust the particle size. Pulverization can be adjusted to the desired particle size and can be performed using industrial grinding mills such as crushers, roller mills, jet mills, or ball mills.

[0078] In one embodiment of the present invention, a lithium-ion secondary battery positive electrode material comprising the above-described additive material for a lithium-ion secondary battery positive electrode is provided. The composite oxide obtained above is used as an additive material and mixed with a lithium-ion secondary battery positive electrode material containing one or more cations selected from Mn, Fe, Ni, and Co to obtain a positive electrode active material. When the additive material and the positive electrode material coexist, they can be mixed using an industrial mixer such as a V-type mixer, screw mixer, or air-flow mixer. Furthermore, heat treatment at 200°C to 400°C can be performed after mixing.

[0079] In one embodiment of the present invention, a lithium-ion secondary battery comprising the above-described lithium-ion secondary battery positive electrode material is provided. When the lithium-ion secondary battery positive electrode material comprising the above-described additive material is used as the positive electrode active material, the negative electrode active material is a carbon material, a lithium-retaining alloy, or other substance capable of lithium retention and release. The electrolyte can be a non-aqueous electrolyte in which a lithium salt is dissolved in a non-aqueous electrolyte or resin. For example, lithium hexafluorophosphate (LiPF6) is used as the lithium salt, and a mixed solution of cyclic carbonate and diethyl carbonate is used as the non-aqueous electrolyte. Furthermore, LiClO4, LiAsF6, LiBF4, LiSO3CF3, LiN(SO3CF3)2, or mixtures thereof are also used as the lithium salt. Furthermore, diethyl carbonate, propylene carbonate, vinylene carbonate, or mixtures thereof can be used as the non-aqueous electrolyte.

[0080] [Example]

[0081] The present invention will now be described with reference to embodiments and comparative examples. However, the present invention is not limited to the embodiments described herein.

[0082] (Example 1)

[0083] The formula Y will be adjusted to the compositional form. 0.3 Zr 0.7 O 1.85Zirconium oxychloride and yttrium chloride were mixed, and the aqueous solution was adjusted. Ammonia was added dropwise to the aqueous solution while stirring to raise the pH, causing co-precipitation and obtaining a precipitate. The solution slurry containing the precipitate was aged at 80°C for 6 hours. The slurry was filtered and washed five times to obtain a cake of precipitate (filter cake). The obtained cake was placed in a crucible and dried at 120°C for 10 hours. The dried sample was calcined at 600°C for 10 hours. The calcined sample was pulverized using a jet ball mill to prepare an additive for the positive electrode of a lithium-ion secondary battery.

[0084] (Examples 2-11)

[0085] In Examples 2 to 11, the aqueous solution was adjusted to become the components shown in Table 1. Furthermore, it was used as an additive material for the positive electrode of a lithium-ion secondary battery under the same conditions as in Example 1.

[0086] (Comparative Example 1)

[0087] In Comparative Example 1, no additives were added; only the positive electrode material was used as the positive electrode active material.

[0088] (Comparative Example 2)

[0089] As a comparative oxide, ZrO2 was prepared. ZrO2 was prepared by dissolving zirconium oxychloride in water in an aqueous solution, then adding ammonia dropwise to the solution while stirring to raise the pH and induce co-precipitation, resulting in a precipitate. The solution slurry containing the precipitate was aged at 80°C for 6 hours. The slurry was then filtered and washed five times to obtain a filter cake. The obtained cake was placed in a crucible and dried at 120°C for 10 hours. The dried sample was then calcined at 600°C for 10 hours. The calcined sample was then pulverized using a jet mill and prepared.

[0090] (Comparative Example 3)

[0091] BaTiO3 was prepared using reagent KZM-50 manufactured by Sakai Chemical Industry.

[0092] (Compare Examples 4 and 5)

[0093] Comparative Examples 4 and 5 were prepared using zirconium oxychloride and chlorides of each element as starting materials, in the manner shown in Table 1, and under the same conditions as in Example 1.

[0094] <Crystal Structure Analysis>

[0095] The obtained samples were evaluated using X-ray diffraction. Samples of lithium-ion secondary battery positive electrode active materials using composite oxides (=additives) were placed in a sample holder and X-ray diffraction measurements were performed using a Rigaku Mini Flex 600 benchtop X-ray diffractometer (CuKα line source) at a 2θ angle range of 20–80°, a step size of 0.02°, and a scan rate of 5° / min.

[0096] <Reactivity with cathode materials>

[0097] To evaluate whether composite oxides can coexist with lithium-ion secondary battery cathode materials, the cathode material (as the parent material) and the composite oxide (as the additive material) were mixed, and X-ray diffraction was used to confirm whether only the diffraction peaks of the cathode material and the composite oxide were observed.

[0098] Compared to LiCoO2 or LiNi 0.5 Co 0.2 M n0.3 O2 and various composite oxides were mixed in a mortar at a mass ratio of 5:1 and calcined at 400°C for 10 hours. The calcined product was then subjected to X-ray diffraction (using a Rigaku MiniFlex600 benchtop X-ray diffractometer with a CuKα line source). X-ray diffraction was performed under the following conditions: 2θ angular range of 20–80°, step size of 0.02°, and scan rate of 5° / min.

[0099] <Evaluation of acid and basic sites>

[0100] Acid and basic sites were determined using a BELCAT-A detector (manufactured by BEL, Japan), to evaluate the amount or temperature of standard material detachment. NH3 was used to evaluate the acid sites, and CO2 was used to evaluate the basic sites. A TCD (Thermal Conductivity Detector) was used. As a pretreatment, the prepared sample was treated at 370°C for 30 minutes in a 20% O2 / He environment, followed by exposure of the standard material at 50°C for 30 minutes to allow adsorption. Subsequently, the temperature was increased from 50°C to 500°C at a rate of 20°C / min, and the amount or temperature of detached standard material was evaluated.

[0101] <Particle Size Distribution Determination>

[0102] The particle size distribution was determined using a particle size analyzer MT3300EXII (manufactured by Microtrac BEL.Corp), and the samples dispersed in a sodium hexametaphosphate solution using an ultrasonic homogenizer (US-300AT, manufactured by Nippon Seiki Co., Ltd.) were evaluated.

[0103] <Specific Surface Area Measurement>

[0104] The specific surface area was determined as follows: As a pretreatment, approximately 0.3 g of the sample was placed in a flask-type sample cell and degassed at 370°C for 40 minutes under nitrogen flow using a FloVac degassing apparatus (manufactured by Anton-Paar Japan). The surface area was then measured using a surface area measuring apparatus (manufactured by Anton-Paar Japan, NOVA touch NX-4LX-1) by the BET method (one-point method) based on nitrogen adsorption.

[0105] <Determination of Dielectric Constant>

[0106] The dielectric constant of the obtained composite oxides was determined at 25°C. An Agilent 4294A (manufactured by Agilent Technologies) was used. Evaluation was conducted in the frequency range of 40 Hz to 110 MHz. The Cole-Cole function was used for fitting, and the Bruggman model was employed to calculate the powder dielectric constant. The relative dielectric constant was calculated as the ratio of the dielectric constants of each composite oxide to the dielectric constant of vacuum.

[0107] <Battery Making>

[0108] The composite oxides and other additives synthesized in each embodiment and comparative example are mixed with the cathode material to adjust the cathode active material. At this time, LiCoO2 and LiNi are used as the cathode materials, respectively. 0.5 Co 0.2 Mn 0.3 O2.

[0109] In Comparative Example 1, no composite oxide was added; the positive electrode material was used as the positive electrode active material to manufacture the battery.

[0110] For Examples 1-11 and Comparative Examples 2-5, 1 mol% of additives such as composite oxides were weighed relative to the positive electrode material and mixed in a mortar. The mixed powder was kept at 400°C for 10 hours, and the resulting calcined powder was used as the positive electrode active material to prepare the positive electrode.

[0111] Acetylene black was used as the conductive additive, and PVdF was used as the binder.

[0112] Weigh the positive electrode active material, conductive additive, and binder in a weight ratio of 7:2:1, and add an appropriate amount of N-methyl-2-pyrrolidone (NMP) to prepare the positive electrode slurry.

[0113] The obtained slurry is coated onto an aluminum current collector, dried, punched into a disc shape, and then pressurized to produce the positive electrode.

[0114] In the embodiments and comparative examples, the positive electrode, negative electrode, and electrolyte were respectively prepared by (layering) lithium metal cut into circular pieces, and by dissolving LiPF6 at 1 mol / L in a solvent in which cyclic carbonate and diethyl carbonate were mixed in a volume ratio of 3:7. The resulting coin-shaped battery CR2032 (diameter 20 mm, height 3.2 mm) was then evaluated and measured.

[0115] <Charge and Discharge Test>

[0116] Charge-discharge tests of coin-shaped lithium-ion secondary batteries using LiCoO2 as the cathode material were conducted using a TOSCAT-3100 (manufactured by Toyo Systems). The coin-shaped lithium-ion secondary batteries were placed in a 25°C constant-temperature bath with a reference capacitance of 1C set to 160mA / g, an upper limit voltage of 4.5V, and a lower limit voltage of 3.3V. The charging rate was 1C, and the discharging rate ranged from 0.1C to 100C, repeated 41 times. The 0.1C rate was tested twice, the 0.2C and 0.5C rates were tested once each, and each rate above 1C was tested 5 cycles. The batteries were left idle for 4 hours before the test. Furthermore, a 1-hour rest period was set after charging and discharging.

[0117] <Degradation Test>

[0118] For LiNi 0.5 Co 0.2 Mn 0.3 A degradation test was conducted on a coin-shaped lithium-ion secondary battery made with O2 as the positive electrode material. The apparatus used was an Electrofield ABE1024-5V. The coin-shaped lithium-ion secondary battery was placed in a constant temperature bath at 45°C, and the reference capacitance 1C was set to 140mA / g. It was charged at a constant current rate of 0.2C until the voltage reached 4.2V, and then charged at a constant voltage for 336 hours.

[0119] Impedance Measurement

[0120] Impedance measurements were performed on coin-shaped lithium-ion secondary batteries after charge-discharge and degradation tests in a constant temperature bath at 20°C using a VSP-300 (manufactured by Biologic).

[0121] For a coin-type lithium-ion secondary battery using LiCoO2 as the positive electrode material, measurements were performed within a range of 4.5V, AC amplitude of 10mV, and frequency of 5mHz to 7MHz. The obtained data were analyzed using... Figure 1 The equivalent circuit shown is fitted to calculate the interfacial charge transfer resistance R of a coin cell with LiCoO2 as the positive electrode active material. LCO and the charge movement resistance R of each battery ct-LCOThe interfacial charge transfer resistance R of a coin-type lithium-ion secondary battery using only LiCoO2 as the positive electrode active material. LCO Based on R, we obtain the relationship with R. ct-LCO The ratio R ct-LCO / R LCO .

[0122] Targeting LiNi 0.5 Co 0.2 Mn 0.3 A coin-type lithium-ion secondary battery, with O2 as the positive electrode material, was tested within a range of 4.2V potential, 10mV AC amplitude, and 10mHz–200kHz frequency. The obtained data were analyzed using… Figure 2 The equivalent circuit shown is fitted to calculate the interface charge transfer resistance R. ct-NCM To use only LiNi 0.5 Co 0.2 Mn 0.3 Interfacial charge transfer resistance R in a coin-type lithium-ion secondary battery using O2 as the positive electrode active material NCM Using this as a benchmark, the relationship between each sample and R is obtained. ct-NCM The ratio R ct-NCM / R NCM .

[0123] [Table 1]

[0124]

[0125] Examples 1-11, as described in Table 1, have a relative permittivity of 20 or higher and include both acid and basic sites, confirming the effectiveness of the present invention. The specific amounts of acid and basic sites in Examples 1-11 are as follows: the amount of acid sites measured at 50°C to 500°C is 0.25 mmol / g or higher, and the amount of basic sites measured at 50°C to 500°C is 0.18 mmol / g or higher. These composite oxides were compared with LiNi... 0.5 Co 0.2 Mn 0.3 The mixture was prepared with O2 at a mass ratio of 5:1 and fired at 400°C for 10 hours. Only substances originating from LiCoO2 or LiNi were observed. 0.5 Co 0.2 Mn 0.3 The diffraction peaks of O2 and the composite oxides of each embodiment were observed. This confirms that these composite oxides do not react with the cathode material containing Ni, Co, Mn, and Fe. Furthermore, Comparative Examples 4-5 also confirmed that the oxides originated from LiCoO2 or LiNi, respectively, which served as the parent material. 0.5 Co 0.2 Mn 0.3Peaks other than those observed by O2 and the additives confirmed the interaction between these additives and LiCoO2 or LiNi. 0.5 Co 0.2 Mn 0.3 O2 reaction.

[0126] By using the compositional formula MxZr 1-x O 2-y The composite oxides of M (elements listed in Table 1) and x = 0.1, 0.5, 0.7, 0.9, etc. can also be used to make materials that satisfy the elements of the present invention, thus confirming the effectiveness of the present invention.

[0127] For each cell, calculate the ratio R of the interfacial charge transfer resistance. ct After / R, it was confirmed that LiCoO2 or LiNi 0.5 Co 0.2 Mn 0.3 When O2 is used as the positive electrode material, the battery using the additive material in the embodiment shows a smaller value than the comparative example. ct A smaller / R value indicates lower charge movement resistance, signifying a gradual improvement in rate characteristics. This further confirms that the composite oxides described in the examples have the effect of improving the rate characteristics of coin-type lithium-ion secondary batteries.

Claims

1. An additive material, used as an additive material for the positive electrode of a lithium-ion secondary battery employing an electrolyte, characterized in that, The additive material comprises a composite oxide that coexists with a lithium-ion secondary battery cathode material containing cations of one or more elements selected from Mn, Fe, Ni, and Co. The composite oxide does not contain alkali metal ions or alkaline earth metal ions, has both acid sites and basic sites, and has a relative permittivity of 20 or higher.

2. The additive material according to claim 1, characterized in that, The composition formula of the composite oxide is as follows: M x Zr 1-x O 2-y Element M contains trivalent metal ions, and the molar ratios x and y satisfy 0 < x < 1 and 0 < y < 0.5, respectively.

3. The additive material according to claim 2, characterized in that, The M comprises one or more trivalent metal ions selected from La, Pr, Sm, Nd, Gd, Yb, Ho, and Y.

4. The additive material according to claim 2 or 3, characterized in that, The M contains a Ce metal ion.

5. The additive material according to claim 1, characterized in that, The specific surface area of ​​the composite oxide is 35 m². 2 / g or more.

6. A positive electrode material for a lithium-ion secondary battery, characterized in that, It contains the additives as described in claim 1.

7. A lithium-ion secondary battery, characterized in that, It includes the lithium-ion secondary battery cathode material as described in claim 6.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2011210694A

  • Positive electrode material for lithium ion secondary battery

    JP2018181614A

  • Lithium ion secondary battery positive electrode material, lithium ion secondary battery positive electrode material additive, lithium ion secondary battery, and method for producing lithium ion secondary battery positive electrode material

    JP2023052895A